2022
DOI: 10.1093/bjsopen/zrac020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the learning curve on survival after laparoscopic liver resection for colorectal metastases

Abstract: Background Laparoscopic liver resection (LLR) is a highly demanding procedure with great variability. Previously published randomized trials have proven oncological safety of laparoscopic liver resection (LLR) as compared to open surgery. However, these were started after the learning curve (LC) was established. This leaves the question of whether the LC of LLR in the early laparoscopic era has affected the survival of patients with colorectal liver metastasis (CRLM). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Researchers also found that surgeons who use LLR must have extensive experience in performing open hepatectomy and that these surgeons will experience a learning curve when performing LLR. The need for a stepwise progression through the learning curve to minimize morbidity and mortality has been highlighted by many centers[ 20 - 22 ]. Furthermore, using laparoscopic surgery for major liver resections and liver resections for lesions adjacent to major vessels has been confirmed to be both feasible and safe[ 23 - 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers also found that surgeons who use LLR must have extensive experience in performing open hepatectomy and that these surgeons will experience a learning curve when performing LLR. The need for a stepwise progression through the learning curve to minimize morbidity and mortality has been highlighted by many centers[ 20 - 22 ]. Furthermore, using laparoscopic surgery for major liver resections and liver resections for lesions adjacent to major vessels has been confirmed to be both feasible and safe[ 23 - 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…As reported, the increase in the volume of LLRs performed in 2009-2012 vs 2000-2008 may be partially attributed to the Louisville 2009 Consensus[ 28 ]. Therefore, approximately 22 out of the total of 160 cases were necessary to overcome the learning curve[ 22 , 29 , 30 ]. A decrease in blood loss during LLR was observed after a minimum of performing 50 cases[ 29 ]; and at least 25 cases were needed to master laparoscopic living donor resection[ 31 ].…”
Section: Discussionmentioning
confidence: 99%